Regionalization of average flow: a brief review of the literature - Santos, Allita Rezende dos; Guimarães, Tainá Thomassim; Mauad, Frederico Fabio; Okawa, Cristhiane Michiko Passos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
The sustainable management of water resources require planning techniques that are dependent on reliable estimates of water bodies flows data. The knowledge of water availability is essential for decision-making; however, data series are generally limited, insufficient and do not cover all places of interest, making it difficult or impossible to carry out strategic water resource planning. In this way, the temporal and spatial gaps can be filled based on robust methodologies. To fill the gaps in the data, spatial information transfer techniques are used, which are called hydrological regionalization. Thus, this article presents a brief bibliographical review, as well as, different applications of the average flow regionalization methods. This method is an important tool to support decision making in the planning and management of water resources. The results found in the researches related to the applicable methodologies of flow regionalization emphasize that the physical, climatic and hydrological diversities of the river basin characteristics require the adoption of specific methods directed to each unit, since the complexity of the ecosystem interactions makes the procedure difficult.